PURCHASE MANAGEMENT INFORMATION SYSTEM DESIGN AT PT. NOP INDONESIA BASED ON DESKTOP APPLICATION - Diana Diana; Genta Sahuri (IT for Society, 2022)
The Purchasing Department is an importantpart of a company when it comes to the procurement of goodsbecause, without a Purchasing Department, the company'soperational continuity can be disrupted. PT. NOP Indonesia asa manufacturing company that produces various kinds offlexible fine packaging made of resin (plastic seeds) requires asystem that can control the availability of raw materials,production equipment, and office supplies to support businessand company operations. The purpose of this system is tofacilitate the process of purchasing goods/items, to help manageand control purchase data, and to assist Purchasing Managers incontrolling and approving purchase documents or data.